Cutting carbon, not the economy - Georg Zachmann (Bruegel, 2012)
A drastic change in the way we produce and consume energy is necessary to contain the risk of global environmental catastrophe. For its part, the EU has set agreed to a greenhouse gas reduction target of 80-95 percent by 2050, compared to 1990. However, with the current fuel mix, even the most ambitious improvements on incumbent technologies are unlikely to be sufficient for reaching the reduction targets. Meeting the targets requires low-carbon transition. However, the process of transition will likely be littered with market failures. Hundreds of more-or-less proven low-carbon technologies are competing for market share in the low-carbon system. In order to bring about the transition to a low-carbon energy and transport system at the lowest cost, policymakers should rely as much as possible on private action to choose, develop, and deploy low-carbon technologies. For those market failures that might only be overcome with technology-specific measures, governments should set up a transparent and predictable mechanism for selecting technologies.
Keywords: 330; EU-Umweltpolitik; EU-Energiepolitik; EU-Verkehrspolitik; Klimaschutz; Treibhausgas; EU-Staaten